2014
DOI: 10.1371/journal.pone.0112084
|View full text |Cite
|
Sign up to set email alerts
|

Functional Vascular Changes of the Kidney during Pregnancy in Animals: A Systematic Review and Meta-Analysis

Abstract: Renal vascular responses to pregnancy have frequently been studied, by investigating renal vascular resistance (RVR), renal flow, glomerular filtration rate (GFR), and renal artery responses to stimuli. Nonetheless, several questions remain: 1. Which vasodilator pathways are activated and to what extent do they affect RVR, renal flow and GFR across species, strains and gestational ages, 2. Are these changes dependent on renal artery adaptation, 3. At which cellular level does pregnancy affect the involved path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 52 publications
1
6
0
Order By: Relevance
“…Numerous studies have examined the renal hemodynamic changes during pregnancy but there is a considerable heterogeneity in their findings that may be explained by the use of invasive methods at different gestational periods [1,22,23]. The changes of GFR and RBF in our rats with NFD ( Fig 5) are similar to that reported in women [6] during gestation.…”
Section: Discussionsupporting
confidence: 78%
“…Numerous studies have examined the renal hemodynamic changes during pregnancy but there is a considerable heterogeneity in their findings that may be explained by the use of invasive methods at different gestational periods [1,22,23]. The changes of GFR and RBF in our rats with NFD ( Fig 5) are similar to that reported in women [6] during gestation.…”
Section: Discussionsupporting
confidence: 78%
“…An impairment of renal glomerular filtration rate has been reported in late gestation in many different species, including ruminants [60], and the massive utilization of amino acids for gluconeogenesis could concur in renal dysfunction of dairy cows during the late gestation [61]. Recent studies performed on monogastric models and humans found high levels of circulating pro-inflammatory cytokines (i.e., tumor necrosis factor alpha, interleukin 1) released during excessive lipid mobilization and uncontrolled inflammation to induce renal artery endothelial dysfunction [62][63][64], thus suggesting also high circulating NEFA and systemic inflammations occurring in dairy cows during TP to play a pivotal role in inducing renal dysfunctions in late gestation.…”
Section: Aloe Improved Kidney Function In Late Gestation and Mitigatementioning
confidence: 99%
“…The latter results from increased arterial and venous resistance by inhibition of endothelial NO‐mediated gestational vasodilatation, sympathetic sensitivity (van Drongelen et al . ) and relaxin (Conrad & Davison, ).…”
Section: Cardiovascular and Renal Characteristics Of Preeclampsiamentioning
confidence: 99%
“…Disrupted endothelial function triggers further impairment of renal function via induction of podocyte dysfunction, with subsequent podocyturia (Craici et al 2014) and increased nephrin concentrations in serum and urine (Jung et al 2017), but also via thrombotic micro-angiopathy (Johnson & Nangaku, 2016). The latter results from increased arterial and venous resistance by inhibition of endothelial NO-mediated gestational vasodilatation, sympathetic sensitivity (van Drongelen et al 2014) and relaxin (Conrad & Davison, 2014).…”
Section: Renal Functionmentioning
confidence: 99%